Content Management Based on Content Popularity Ranking in Information-Centric Networks - Nazib Abdun Nasir; Seong-Ho Jeong (Applied Sciences, 2021)
Users can access the Internet anywhere they go at any time due to the advancement of communications and networking technologies. The number of users and connected devices are rapidly increasing, and various forms of content are becoming increasingly available on the Internet. Consequently, several research ideas have emerged regarding the storage policy for the enormous amount of content, and procedures to remove existing content due to the lack of storage space have also been discussed. Many of the proposals related to content caching offer to identify the popularity of certain content and hold the popular content in a repository as long as possible. Although the host-based Internet has been serving its users for a long time, managing network resources efficiently during high traffic load is problematic for the host-based Internet because locating the host with their IP address is one of the primary mechanisms behind this architecture. A more strategical networking paradigm to resolve this issue is Content-Centric Networking (CCN), a branch of the networking paradigm Information-Centric Networking (ICN) that is focused on the name of the content, and therefore can deliver the requested content efficiently, securely, and faster. However, this paradigm has relatively simple content caching and content removal mechanisms, as it caches all the relevant content at all the nodes and removes the content based on the access time only when there is a lack of space. In this paper, we propose content popularity ranking (CPR) mechanism, content caching scheme, and content removal scheme. The proposed schemes are compared to existing caching schemes such as Leave Copy Everywhere (LCE) and Leave Copy Down (LCD) in terms of the Average Hop Count, content removal schemes such as Least Recently Used (LRU) and Least Frequently Used (LFU) in terms of the Cache Hit Ratio, and finally, the CCN paradigm incorporating the LCE and the LRU schemes and the host-based Internet architecture in terms of Content Delivery Time. Graphical presentations of performance results utilizing the proposed schemes show that the proposed CPR-based schemes for content caching and content removal provide better performance than the host-based Internet and the original CCN utilizing LCE and LRU schemes.